2020
DOI: 10.2298/tsci190625339u
|View full text |Cite
|
Sign up to set email alerts
|

The 3-D flow of Casson nanofluid over a stretched sheet with chemical reactions, velocity slip, thermal radiation and Brownian motion

Abstract: The 3-D flow of Casson nanofluid over a stretched sheet with chemical reactions, velocity slip, thermal radiation, and Brownian motion have been analyzed. By employing the similarity transformation, the ODE are obtained from the fluidic system PDE. The transformed ODE are handled for the numerical solution of the proposed fluidic problem by incorporating shooting technique. To compare the obtained numerical results, Lobatto 111A method has been implemented, with 5-8 decimal places of accuracy. The numerical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Although bvp4c is a built‐in function, still we have validated our results in limiting cases with published works. The numerical values are compared with Hayat et al, 28 Freidoonimehr and Rahimi, 37 and Umar et al, 38 and these valid agreements are found with the existing values and present ones (see Table 1).…”
Section: Methodssupporting
confidence: 84%
“…Although bvp4c is a built‐in function, still we have validated our results in limiting cases with published works. The numerical values are compared with Hayat et al, 28 Freidoonimehr and Rahimi, 37 and Umar et al, 38 and these valid agreements are found with the existing values and present ones (see Table 1).…”
Section: Methodssupporting
confidence: 84%
“…In the future, the designed ANN-PSOIPA can be functional to apply to the biological models [58,59] and fluid dynamics models [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…So MWNN is the best choice to solve such complicated models using the global and local search terminologies GAIPA. In future, MWNN-GAIPA can be implemented to solve the fluid dynamic nonlinear systems, biological nonlinear systems, singular higher order differential systems, fractional processing, direction of arrival estimation, power and eneggy systems [53][54][55][56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%